THE ECONOMIC BURDEN OF SMOKING-ATTRIBUTABLE DISEASES TO THE GOVERNMENT HEALTHCARE EXPENDITURES IN TOLITOLI DISTRICT 2014 - Egi Abdul Wahid1, Yurdhina Meilissa2, and Olivia Herlinda2 (MTCC, John Hopkins n The Union, 2016)
Background: The economic loss caused by smoking attributable expenditures in Indonesia is six times higher than the income generated by tobacco taxes. A policy that can be used to reduce the economic burden caused by tobacco related diseases might be a prohibition of tobacco advertising in the local jurisdiction that may lead to a decrease in the number of new smokers However, many local government might be an assumption on the part of the local government that their local revenue will decrease significantly if this policy is implemented. Tolitoli is part on Central Sulawesi Province, which is underdeveloped city with small local revenue, Tolitoli have high smoking prevalence 38,2% is higher than national average and always increase each years. Methods: This research aimed to assess the health care expenditures incurred by in-patients who were diagnosed with tobacco related diseases and compare it with the local revenue generated by tobacco advertising in Tolitoli district. This research was a cross-sectional research and was conducted by examining and analyzing relevant documents. Prevalence-based approach was used as the method of the study and smoking attributable fraction used for calculating economic burden. The hospital data for this research was collected from Hospital Tolitoli (RSUD) for 1126 patients in 2012 and 769 patients in 2013 that were diagnosed with tobacco related diseases. Results: Results show that both in 2012 and 2013, the tobacco advertisement tax contributed to just 0.014% out of the total local government revenue. In fact, the government expenditures for patients who were treated for tobacco related diseases in 2012 and 2013 was 2.1 and 1.3 times more than the total income generated by tobacco advertisements . These data showed that the tobacco tax revenue had much negative impact than the benefits. Conclusions: We therefore, suggest the local government consider prohibiting tobacco advertisements and any kind of promotions undertaken by the tobacco industry through their corporate social responsibility or CSR activities. In addition, consider stopping the issuance of new permits in Tolitoli and not renew? Existing tobacco advertising licenses. Keyword: Government Local Revenue, Smoking Attributable Expenditures, Smoking attributable disease, Tobacco Advertising